Factors associated with iron deficiency anaemia among pregnant women attending selected health clinics in Selangor and Kuala Lumpur, Malaysia - Tan, Meng Lee (2021)
Iron deficiency anaemia (IDA) is defined as the presence of anaemia (Hb<11 g/dL) and iron deficiency (SF<15μg/L), which is a major health problem during pregnancy leading to adverse impacts on maternal and infant health. The crosssectional study aimed to determine the factors associated with IDA in 400 third trimester pregnant women from six randomly selected health clinics in Selangor and Kuala Lumpur was carried out. Socio-demographic characteristics and knowledge on dietary iron supplementation and anaemia were assessed using a set of standardised questionnaire via face-to-face interviews. Information on obstetrical characteristics was obtained using secondary data from the antenatal medical record. Dietary practices were assessed using a semi-quantitative food frequency questionnaire. Information on haemoglobin (Hb) was obtained using secondary data from the antenatal medical record and serum ferritin (SF) was obtained from 1mL of venous blood sample drawn by trained nurse and analysed using ADVIA Centaur analyser for the determination of iron status. Bivariate analyses and multiple logistic regression were performed to determine the associations between socio-demographic characteristics, obstetrical characteristics, dietary practices, knowledge on dietary iron supplementation and anaemia as well as IDA. The prevalence of IDA was 15.2%, with mean + standard deviation Hb of 11.12+1.01 g/dL and median (interquartile range) SF of 27.40 (32.20) μg/L. IDA were significantly associated with pregnant woman of Malay ethnicity (OR=8.693, 95% CI=1.079-70.022, p=0.042), spouse of older age (OR=1.077, 95% CI=1.021-1.136, p=0.007), who had pre-pregnancy underweight (OR=3.105, 95% CI=1.363-7.074, p=0.007) and non-compliant towards dietary iron supplementation (OR=3.415, 95% CI=1.792-6.508, p<0.001), explaining 15.4% of the variances in IDA. Findings of the present study suggested that Malay women who had pre-pregnancy underweight and non-compliant towards dietary iron supplementation should be targeted for assessments of iron status during antenatal care visits. Pregnant women whose spouses of older age should also be targeted so that preventive and intervention measures against IDA could be taken as required.